PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA GAMBAR DAN LKPD UNTUK MENINGKATKAN HASIL BELAJAR IPAS - Abu Zaeni; Khoiruzzaim Kurniawan; Rahmi Seri Nada; Ammi Thoibah Nst; Hasnah Fauziah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
This study aims to improve the learning outcomes of Natural and Social Sciences (IPAS) on the topic of natural and artificial landscapes through the application of the Problem Based Learning (PBL) model assisted by picture media and student worksheets (LKPD) among third-grade students of MI Taufiqiyatul Asna, Kepung, Kediri. This research is a Classroom Action Research conducted in two cycles following the Kemmis and McTaggart model, comprising planning, acting, observing, and reflecting. The subjects were 35 students. Data were collected through learning-outcome tests, observation, and documentation, then analyzed descriptively and quantitatively. The results show a significant improvement. In the pre-cycle stage, classical mastery reached only 45.7% with an average score of 71.1. After applying the PBL model, mastery increased to 85.7% with an average of 87.3 in cycle I, and reached 97.1% with an average of 97.4 in cycle II. These findings indicate that the application of the Problem Based Learning model assisted by picture media and LKPD is effective in enhancing students’ activeness, cooperation, and conceptual understanding. Therefore, this model can serve as a contextual and meaningful alternative strategy for teaching IPAS in Islamic elementary schools.